Evolution of microscopic domains in Co/Pt multilayers with perpendicular magnetic anisotropy - Quach, Duy Truong (Hue University Journal of Science: Natural Science, 2025)
We investigated the domain evolutions of (0.3nm Co/0.8nm Pt)n multilayers (n = 5 and 10) with perpendicular magnetic anisotropy. Our direct observation of magnetic domain structures by means of magneto-optical microscopy reveals that under a negative magnetic field, domain evolution happens via domain wall motion at the domains’ boundaries. However, under a reversed field, the domains react differently depending on their domains’ substructures. While the domains shrink solely at their boundaries when n = 5, the domain wall motion was observed mostly inside the domains’ boundaries when n = 10. This could offer an effective way of using magneto-optical microscopy to investigate domain structures of multilayers with fine substructures without using other high-resolution observation methods.